Cytomegalovirus Replication in Cells Pretreated with 5-Iodo-2′-Deoxyuridine - Jeor, Stephen St. (1973)
The replication of human cytomegalovirus (CMV) in cells pretreated with 5-iodo-2′-deoxyuridine (IUdR) was studied. Pretreatment of cells with IUdR enhanced several parameters of virus replication. Virus grown in drug-treated cells exhibited a shorter eclipse period and the cells produced more infectious virus sooner than did untreated cells. There was an approximate fivefold increase in virus yield per cell in the drug-treated samples when compared to control cultures. The time required for plaque development was shortened by 6 days in drug-treated cultures. Pretreatment of cells with IUdR also increased plaquing efficiency of the virus by approximately 10-fold. The enhancement of virus replication by IUdR was further demonstrated by varying the multiplicity of infection. In a 7-day period there was a 100-fold increase in sensitivity of the cultures for virus detection when the cells had been previously exposed to IUdR. The data presented indicate the possibility that IUdR interferes with the production of a cellular product inhibitory for CMV replication.